Impact of jaguar Panthera onca (Carnivora: Felidae) predation on marine turtle populations in Tortuguero, Caribbean coast of Costa Rica - Arroyo-Arce, Stephanny (2015)
Little is known about the effects of jaguars on the population of marine turtles nesting in Tortuguero National Park, Costa Rica. This study assessed jaguar predation impact on three species of marine turtles (Chelonia mydas, Dermochelys coriacea and Eretmochelys imbricata) that nest in Tortuguero beach. Jaguar predation data was obtained by using two methodologies, literature review (historical records prior the year 2005) and weekly surveys along the 29 km stretch of beach during the period 2005-2013. Our results indicated that jaguar predation has increased from one marine turtle in 1981 to 198 in 2013. Jaguars consumed annually an average of 120 (SD= 45) and 2 (SD= 3) green turtles and leatherbacks in Tortuguero beach, respectively. Based on our results we concluded that jaguars do not represent a threat to the population of green turtles that nest in Tortuguero beach, and it is not the main cause for population decline for leatherbacks and hawksbills. Future research should focus on continuing to monitor this predator-prey relationship as well as the factors that influence it so the proper management decisions can be taken.